PENERAPAN DAN PEMANFAATAN MEDIA ONLINE DALAM PENGEMBANGAN SISTEM PEMASARAN UMKM (AGROINDUSTRI) DI KABUPATEN JEMBER - Yoga Satria Siaga; Jani Januar; Ati Kusmiati (UNEJ e-Proceeding, 2018)
The development of online media in the digitalization era has an influence on the direction of changes in economic structure. This research was conducted in Jember Regency, East Java, especially for MSMEs who were registered with the Cooperative and MSME Office of Jember Regency. The goal to be achieved is to provide an overview of the application of online media which is divided into 6 (six) levels. MSME players in the Jember region possess their respective characteristics which are differentiated by stage / stage. The use of online media in each of those used by MSME actors also brings benefits. The benefits of using online media are divided into 15 (fifteen). At a certain level the benefits of using online media are significant, but some others do not have much impact.